AN ANALYSIS OF STUDENTS’ NEEDS OF SPEAKING MATERIALS AT ENGLISH EDUCATION STUDY PROGRAM - Ningsih, Tika Wahyu Prihati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
The study aims to find out the Students needs of Speaking Materials at English Education Study Program in UIN Sultan Thaha Saifuddin Jambi. The method of the research is qualitative. The subject of this research were five semester students at English Education Study Program in UIN Sultan Thaha Saifuddin Jambi. This research data were collected using interview. The findings of the research showed that, students need Audio visual such as watching videos, watching film, and listening to music. Students prefer learning by using the media. To help them follow the process of learning, it can help students to improve and their speaking skill.